Factors affecting weight gain velocity in preterm infants getting kangaroo mother care in hospital and after discharge from neonatal intensive care unit - Yasmin, Faria; Asaduzzaman; Wahab, Afrina; Kamrul Hassan Shabuj, Mohammad (International Journal of Contemporary Pediatrics, 2025)
Background: Preterm neonates with low birth weight are at heightened risk of suboptimal postnatal growth. kangaroo mother care (KMC) has proven to enhance neonatal survival, growth, and development. However, various maternal and neonatal factors may influence weight gain during KMC. Objective was to identify factors affecting weight gain velocity in preterm neonates receiving KMC. Methods: This prospective observational study was conducted in the neonatal intensive care unit (NICU) of BMU from March 2022 to August 2023. Hemodynamically stable preterm neonates weighing ≤2000 gm who fulfilled inclusion and exclusion criteria were enrolled. Neonatal weights were recorded during hospitalization and weekly for four weeks post-discharge. Weight gain velocity at the fourth week was calculated, and factors influencing weight gain were analysed. Results: Of 82 enrolled neonates, 66 completed four weeks of follow-up. The mean weight gain velocity was 15.05±3.57 gm/kg/day, with 57.6% achieving adequate gain (≥15 gm/kg/day). The adequate gain group started KMC earlier (3.61±1.57 versus 6.54±2.94 days, p<0.001), had longer daily KMC duration (5.55±0.83 versus 4.58±0.79 hours, p<0.001), and more total KMC days (33.84±3.83 versus 31.57±3.17 days, p=0.013). KMC interruptions were significantly higher among those with inadequate gain (60.7% versus 21.1%, p=0.001). Multivariate logistic regression identified earlier initiation, longer daily duration, and more total KMC days as positive predictors of weight gain, while interruptions negatively impacted growth. Conclusions: Early initiation, longer duration, and uninterrupted KMC significantly improve weight gain velocity in preterm neonates both during hospital stay and after NICU discharge.